2021
DOI: 10.3390/ani11030761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Doses of Condensed Tannins Extract from Cistus ladanifer L. on In Vitro Ruminal Fermentation and Biohydrogenation

Abstract: Cistus ladanifer (rockrose) is a perennial shrub quite abundant in the Mediterranean region, and it is a rich source in secondary compounds such as condensed tannins (CTs). Condensed tannins from C. ladanifer were able to change the ruminal biohydrogenation (BH), increasing the t11–18:1 and c9,t11–18:2 production. However, the adequate conditions of the C. ladanifer CTs used to optimize the production of t11–18:1 and c9,t11–18:2 is not yet known. Thus, we tested the effect of increasing the doses of C. ladanif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…The adverse impact of the tannins on the fermentation has been reported, particularly when supplemented at such high levels (Kumar and Vaithiyanathan, 1990). In a recent study, Guerreiro et al (2021) reported that condensed tannin adversely impacted volatile fatty acid production; however, the adverse impact was more pronounced at higher doses (75-100 g/kg DM). The concentration of tannins (10.4 g/kg DM) in the HD treatment Alpha and beta diversity plots of bacteria (A,B) and archaea (C,D).…”
Section: Discussionmentioning
confidence: 99%
“…The adverse impact of the tannins on the fermentation has been reported, particularly when supplemented at such high levels (Kumar and Vaithiyanathan, 1990). In a recent study, Guerreiro et al (2021) reported that condensed tannin adversely impacted volatile fatty acid production; however, the adverse impact was more pronounced at higher doses (75-100 g/kg DM). The concentration of tannins (10.4 g/kg DM) in the HD treatment Alpha and beta diversity plots of bacteria (A,B) and archaea (C,D).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis of the language of the clusters provide an idea of the main research topic covered by each of them. Cluster 0, the smallest cluster with only 6% of the total articles (99 articles), brings together articles that deal mainly with the effect of tannins present in plants of the Cistus genus, especially C. ladanifer, that certain ruminants, such as goats, consume in their diet, since there are indications that relate the levels of these phenols with better health and quality of these animals' meat and milk [12][13][14][15]. Cluster 1, the second-largest cluster with 31% of the total articles (489 articles), groups articles that address the bioactive and medicinal properties of the extracts and essential oils obtained from Cistus, such as its antioxidant and antibacterial capacity [6,16,17].…”
Section: Article Clusteringmentioning
confidence: 99%
“…These FA are considered as potential indicators of the abundance and activity of microbial groups, and therefore may reflect the effects of the chemical composition of the concentrate in the ruminal environment. The negative effects of secondary compounds (i.e., CTs) have been reported on the OBCFA concentrations in digesta or even on volatile FA concentration, suggesting modifications in bacterial activity [ 6 , 41 ]. These previous findings support our observations, since lambs from the Cp groups tended ( p = 0.059) to have decreased levels of C15:0 in IMF.…”
Section: Resultsmentioning
confidence: 99%